(untitled) - Eun, Cheol S. (Boston, Mass., 1998)
The overriding objective of the text is to teach students how to be effective global financial managers. The text covers the fundamentals of the macroeconomic environment of international financial management, discusses the financial environment in which the multinational firm and its managers must function, and covers foreign exchange management and financial management in a multinational firm.
Keywords: International finance,International business enterprises,Foreign exchange,Financial institutions, International,Tổ chức tài chính, quốc tế,Doanh nghiệp kinh doanh quốc tế,Trao đổi quốc tế,Tài chính quốc tế; Finance,Tài chính